Analisis Kemampuan Komunikasi Matematis Siswa dalam Menyelesaikan Soal pada Materi Teorema Pythagoras - Tajrumi, Atha Nadiyah; Murni, Atma; Roza, Yenita (Jurnal Gantang, 2025)
Mathematical communication skills are essential for learning mathematics. Nevertheless, many students still demonstrate low proficiency, particularly among junior high school students. This study aimed to describe and analyze students' mathematical communication abilities regarding the Pythagorean theorem. The research employed a descriptive qualitative approach with a sample of 20 eighth-grade students at SMPN 2 Pekanbaru. Data were collected using a mathematical communication ability test in problem-solving. The test consisted of three essay questions based on indicators of mathematical communication skills. Data analysis techniques included data reduction, data presentation, and concluding. The results indicate that the mathematical communication ability of eighth-grade students at SMPN 2 Pekanbaru on the Pythagorean theorem topic falls into the low category, with an average score of 32.91. Based on the test indicators, the ability to represent everyday problems using mathematical language was categorized as low (26%). Interpreting images into mathematical symbols and language was moderate (43%), while presenting statements into mathematical models was also low (28%). These findings indicate that students are not yet able to communicate their mathematical thinking processes in a coherent manner. The implication is that instructional practices should provide opportunities for students to explain their problem solving steps and consistently engage in mathematical communication during classroom activities.